Meiocyte-Specific and AtSPO11-1–Dependent Small RNAs and Their Association with Meiotic Gene Expression and Recombination - Huang, Jiyue (Plant Cell, 2019)
Meiotic recombination ensures accurate chromosome segregation and results in genetic diversity in sexually reproducing eukaryotes. Over the last few decades, the genetic regulation of meiotic recombination has been extensively studied in many organisms. However, the role of endogenous meiocyte-specific small RNAs (ms-sRNAs; 21–24 nucleotide [nt]) and their involvement in meiotic recombination are unclear. Here, we sequenced the total small RNA (sRNA) and messenger RNA populations from meiocytes and leaves of wild type Arabidopsis (Arabidopsis thaliana) and meiocytes of spo11-1, a mutant defective in double-strand break formation, and we discovered 2,409 ms-sRNA clusters, 1,660 of which areSPORULATION 11-1 (AtSPO11-1)–dependent. Unlike mitotic small interfering RNAs that are enriched in intergenic regions and associated with gene silencing, ms-sRNAs are significantly enriched in genic regions and exhibit a positive correlation with genes that are preferentially expressed in meiocytes (i.e. Arabidopsis SKP1-LIKE1 and RAD51), in a fashion unrelated to DNA methylation. We also found that AtSPO11-1–dependent sRNAs have distinct characteristics compared with ms-sRNAs and tend to be associated with two known types of meiotic recombination hotspot motifs (i.e. CTT-repeat and A-rich motifs). These results reveal different meiotic and mitotic sRNA landscapes and provide new insights into how sRNAs relate to gene expression in meiocytes and meiotic recombination.